THE EFFECT OF GOVERNMENT INTERNAL CONTROL SYSTEM ON FRAUD PREVENTION (CASE STUDY ON FAMILY HOPE PROGRAM OPERATOR TASIKMALAYA) - Yuniarti, Rita; Arroisi, Najiya; Arifta, Sugih Bhakti; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
Fraud is a crime that can certainly harm various elements because it is carried out with various dishonest actions for the benefit of oneself or a group of people. The main thing to prevent fraud is to create reliable internal control, whether in the various concepts of the control structure or in terms of its implementation. All levels of the organization related to the control structure must be committed to participating in preventing fraud. In 2021, a fraud case in the PKH Social Assistance was found by one of the PKH Facilitators worth Rp. The purpose of this research is to find out how the Government's Internal Control System can affect fraud prevention. The research sample was taken using Convenience Sampling. The data that is used as a reference and used in the study is primary data in the form of questionnaires and then measured with a Likert scale. Questionnaires were distributed to all samples and 102 samples were returned to the questionnaire, then this data was processed. Meanwhile, the data analysis in this study is a simple linear regression analysis and results in research that the government's internal control system has a positive influence on fraud prevention.